On the Scaling of Anthropometric Test Device (ATD) Finite Element Models - Rafukka, Ibrahim; Sahari, Barkawi; Abdulaziz. A. Nuraini; Manohar, Arumugam (Journal of Automotive Powertrain and Transportation Technology, 2024)
Crash dummies are the tools used to represent human beings in the assessment of vehicle safety performance. Current crash dummies are produced using US anthropometric data and children of various ages are not represented. This paper presents the application of morphing technique in generating crash dummy models to a given anthropometric data. The method was described using Hybrid III 3YO dummy model as an example. Morphing operation was applied to scale down the anthropometric dimensions of six year old Hybrid III (6YO HIII) dummy finite element (FE) model to that of three year old Hybrid III (3YO HIII). The morphed model was validated by comparing its biomechanical response data against experimental and simulation results from literature in a sled test based on the specification of Federal Motor Vehicle Safety Standard (FMVSS 213). The simulation results were found to be in good correlation with experimental and simulation results of sled test carried out using 3YO HIII dummy both qualitatively and quantitatively in x-head acceleration, x-chest acceleration and resultant upper neck moment and force. The curves of all the quantities show similarities in trends and the peak values were reasonably comparable to those in the literature results. The technique described in this study is therefore useful in developing child dummy for various age groups, percentiles as well as subject specific from existing FE model with short design time and reduced cost. The new dummy model developed could be used to evaluate three year old child injuries in motor vehicle crash simulations.